Molecular Identification of a Moricin Family Antimicrobial Peptide (Px-Mor) From Plutella xylostella With Activities Against the Opportunistic Human Pathogen Aureobasidium pullulans - Xu, Xiaoxia; Zhong, Anqiao; Wang, Yansheng; Lin, Boda; Li, Peng; Ju, Wenyan; Zhu, Xiaojia; Yu, Jing; De Mandal, Surajit; Jin, Fengliang (Frontiers in Microbiology, 2019)
Antimicrobial peptides (AMPs) represent the largest group of endogenous compounds and serves as a novel alternative to traditional antibiotics for the treatment of pathogenic microorganisms. Moricins is an important α-helical AMP plays a crucial role in insect humoral defense reactions. Present study was designed to identify and characterize novel AMP moricin (Px-Mor) from diamondback moth (Plutella xylostella) and tested its activity against the opportunistic human pathogen Aureobasidium pullulans. Molecular cloning of Px-Mor using rapid amplification of cDNA ends (RACE) revealed 482 bp full length cDNA with 198 bp coding region. The deduced protein sequence contained 65 amino acids with a molecular mass of 4.393kDa. Expression analysis revealed that Px-Mor was expressed throughout the life cycle of P. xylostella with highest in 4th instar and prepupa stage and played different roles at different developmental stages. Tissue specific distribution showed that Px-Mor was highly expressed in fat body and hematocyte. In vitro, antimicrobial assays indicated that Px-Mor exhibited broad spectrum antimicrobial activity against Gram positive bacteria (GPB), Gram negative bacteria(GNB)as well as in fungi. Moreover, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) revealed that Px-Mor can cause obvious morphological alterations in A. pullulans, which demonstrated its powerful effect on the mycelial growth inhibition. Taken together, these results indicate that Px-Mor plays an important role in immune responses of P. xylostella and can be further exploited as an antimicrobial agent against various disease including for the treatment of A. pullulans infection.